1991
DOI: 10.1295/polymj.23.1371
|View full text |Cite
|
Sign up to set email alerts
|

Gas Permeation through Poly(N-n-alkylmaleimide) Membranes

Abstract: ABSTRACT:The permeation of oxygen and nitrogen through the membranes of poly-(N-n-alkylmaleimide )s including poly(N-n-butylmaleimide) [poly(nBMI)] and poly(N-dodecylmaleimide) [poly(DodMI)] was investigated. These membranes from polymaleimides have been revealed to have high permeability coefficients even under their glass transition temperatures on account of facile permeation through the fused alkyl chain in the side group. The apparent diffusion coefficient was determined to be greater than 10-6 cm 2 s-1 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…4,23 The PhMI with 2-alkoxycarbonyl substituents also showed similar polywere determined by thermogravimetric analysis in a nitrogen stream at a heating rate of 10ЊC/ merization behaviors. 24,25 The slightly higher reactivity of 3TFPhMI than of 4TFPhMI, as seen in min. The decomposition temperatures determined are summarized in Table III, together with the Table I and Figure 2, is interpreted as an electronic effect; namely, a para-trifluoromethyl group is a previous results for poly(MPhMI)s. 4 It has been revealed that poly(TFPhMI)s have stronger electron-withdrawing group than that in the meta position.…”
Section: Solubility Of Polymersmentioning
confidence: 99%
“…4,23 The PhMI with 2-alkoxycarbonyl substituents also showed similar polywere determined by thermogravimetric analysis in a nitrogen stream at a heating rate of 10ЊC/ merization behaviors. 24,25 The slightly higher reactivity of 3TFPhMI than of 4TFPhMI, as seen in min. The decomposition temperatures determined are summarized in Table III, together with the Table I and Figure 2, is interpreted as an electronic effect; namely, a para-trifluoromethyl group is a previous results for poly(MPhMI)s. 4 It has been revealed that poly(TFPhMI)s have stronger electron-withdrawing group than that in the meta position.…”
Section: Solubility Of Polymersmentioning
confidence: 99%
“…Copolymerizations of N‐substituted maleimides with various vinyl monomers have been investigated by many authors 21–27. Specifically, copolymerization with electron‐donor monomers such as styrene is well‐known to yield alternating copolymers, and the copolymerization mechanism has been discussed by others 26–29…”
Section: Introductionmentioning
confidence: 99%
“…When the copolymerization was performed using a large excess amount of VE, the alternating copolymers ( P1a ‐ P1c ) were produced (Scheme ). A difference in the molecular conformation of the N ‐phenyl moieties had no effect on the reactivity during the alternating copolymerization of the RPhMIs with VE under the conditions shown in Table , while it was reported in the literature that the reactivity of the RPhMIs was suppressed by the introduction of bulky alkyl groups into the ortho positions during the homopolymerization and copolymerizations with St and MMA . All the copolymers with VE were revealed to have high onset temperatures for decomposition ( T d5 =342 °C–346 °C) [Figure (a)] and high T g values in the range of 128 °C–151 °C (See Table ).…”
Section: Resultsmentioning
confidence: 93%